Is gut microbiota associated with Parkinson’s disease? - A. V. Tyakht; V. M. Alifirova; N. G. Zhukova; I. A. Zhukova; A. V. Latypova; O. P. Izhboldina; V. A. Petrov; Yu. S. Mironova; M. A. Titova; M. A. Nikitina; E. S. Kostryukova; Yu. B. Dorofeeva; et al. (Бюллетень сибирской медицины)
Parkinson’s disease (PD) is a neurodegenerative disorder with a complex pathogenesis. Today more and more studies are focusing on microbiota-gut-brain axis searching the causes of neurodegenerative and neuroinflammatory processes.The aim of our study is to determine the relationship between the composition of gut microbiota and clinical manifestations of PD.Materials and methods. We examined 89 patients with a PD diagnosis. Clinical assessment was performed including medical history collection, rating disease stage using Hoehn and Yahr scale. Motor and nonmotor symptoms as well as possible complication were examined using the Unified Parkinson’s Disease Rating Scale. In addition, patients were asked to fill in Parkinson’s Well-Being Map and defecation diary that included Bristol scale. DNA isolation was performed in accordance with the method described. Preparation of libraries and amplicon sequencing of marker variable region V3–V4 of bacterial 16S rRNA genes was performed with MiSeq device (Illumina, USA) according to manufacturer’s standard protocol. Filtering readings by quality and their taxonomic classification were carried out using QIIME version 1.9.0 software. The assessment of statistical differences in abundance of taxonomic units among the groups of patients was performed using IBM SPSS Statistics 23.1 software.As a result, we have identified significant differences in the abundance of seven genera among the groups of patients with different forms of the disease. We identified about 40 genera constituting 54.8% of the intestinal microbiota, that had a correlation with the clinical manifestations of the disease. These microorganisms might be involved in the pathogenesis of PD and, thus, require more clinical research in the light of emerging new methods of altering microbiotic composition by correcting dysbiosis to improve disease management and outcome.